Near-freezing temperature storage improves shelf-life and suppresses chilling injury in postharvest apricot fruit (Prunus armeniaca L.) by regulating cell wall metabolism. (1st September 2022) - Li, Yaling; Zhao, Yating; Zhang, Zhicheng; He, Huan; Shi, Ling; Zhu, Xuan; Cui, Kuanbo
Highlights: Near freezing temperature (NFT) storage mitigating the occurrence of chilling injury. NFT storage suppresses the activity of cell wall degrading enzymes. NFT storage delays degradation of pectin, cell wall and chloroplast. NFT storage improved the quality of apricots during storage and shelf life. Chilling resistance in NFT storage is related to the content of polysaccharides. Abstract: To avoid chilling injury (CI) of apricots during storage, 1–2 °C and 4–6 °C storage as controls, the relationship between changes in cell wall characteristics and the occurrences of chilling injury under near-freezing temperature (NFT) storage was studied. NFT-stored improved apricots quality and inhibited CI index, membrane permeability and malondialdehyde (MDA) content; This also significantly inhibited the activity of cell wall modifying enzymes, delaying the solubilization of water-soluble pectin (WSP) and the degradation of cellulose. Transmission electron microscopy (TEM) imaging revealed that the density of the middle lamella in stored for 49 d was higher NFT than controlled temperature, delaying cell wall and chloroplast disintegration. Additionally, NFT-stored has no CI during the shelf life, and can be normal after ripening, maintaining higher commodity rate and sensory characteristics. These conclusions show that NFT storage can effectively improve the cold resistance of apricot fruit.